Perancangan Mesin Pengupas Kulit Kentang Dengan Metode VDI 2221 - Rifki Dermawan; Aldi Wibowo (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT Designing a product means describing the ideas you have to solve a problem. By using the VDI 2221 method to design a product, there are at least 3 points that are included in the works that are made realistic, aesthetic, and ergonomic. In the manufacture of potato peeler machine aims to help business people with a simple way of working and low production costs. then the purpose of designing this potato peeler machine is to make an innovation of a potato peeler that is practical, energy efficient and inexpensive, to know the process of peeling the machine, to know the components and functions of the tool. With the VDI 2221 design method as the method used to solve problems and optimize the use of raw materials and production processes. In this method there are several stages of design between wish list, concept design, design of form and detailed design. The potato peeler machine is designed using solidwork for 3D. The step of making a potato peeler starts from determining the design of the tool, determining the main components, the process of designing the process of making a potato peeler tool. Keywords: Potato Peeler Machine, VDI 2221 Method